Digital monitoring and modeling of activities:the IVFC case study - Xingkai SUN; Xiao WANG; Hao LU (智能科学与技术学报)
At present,the frequency of various activities,such as competitions and conferences is increasing day by day.However,there is a lack of an effective platform of digital monitoring and analysis of online media for such events.Based on the method framework in parallel intelligence and knowledge automation theory,a methodological framework for network media monitoring and modeling analysis for events was proposed in this paper,and takes the “Intelligent Vehicle Future Challenge” as an application example.The dataset was collected from three main types of online media (news,WeChat,Weibo) data from 2009 to 2017.Then the online media data were analyzed and visualized from the multiple dimensions including time and space,hotspots,release sources,keywords,topics,semantics,and entities.The results show that the relevant framework can provide effective digital monitoring means and auxiliary decision support for the activity-related organizations.